Experimental Performance Testing Of The Actuation Part Of Piezoelectric Generator For Alternative Power Generation - S.N.S, Jamaludin; R. A., Bakar (2010)

(untitled)
Piezoelectricity was noticed as a new potential in the alternative power generation field. A new design of piezoelectric generator prototype was developed in this project within an innovation idea on the actuation concept of the inner part that makes the system working. This paper will show the experimental testing procedure to reach the performance of the new system developed. The independent variables used for the experiment are magnitude, speed and durations and they come in some different values. These values show different results and explain the performance of the actuation part developed